2020
DOI: 10.1101/2020.02.28.968834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spo0A suppressessinlocus expression inClostridioides difficile

Abstract: 24Clostridioides difficile is the leading cause of nosocomial infection and is the causative 25 agent of antibiotic-associated diarrhea. The severity of the disease is directly associated 26 with the production of toxins, and spores are responsible for the transmission and 27 persistence of the organism. Previously we characterized sin locus regulators SinR and 28SinR', where SinR is the regulator of toxin production and sporulation, while the SinR' 29 acting as its antagonist. In Bacillus subtilis, Spo0A, the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…SinR and SinR' are transcribed as a single transcript and has not been associated with the control s B expression, nor has a s B promoter been identified upstream of the locus. The sinRR' expression can be supressed by Spo0A, as a phosphorylated Spo0A (Spo0A~P) can bind to the only promoter sequence upstream of this locus 53 . While this locus and s B may contribute to DrsbW phenotypic responses, SinR regulates the transcription of other pleiotropic regulators such as s D , Spo0A and CodY, which can regulate many other genes in C. difficile 39,[54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SinR and SinR' are transcribed as a single transcript and has not been associated with the control s B expression, nor has a s B promoter been identified upstream of the locus. The sinRR' expression can be supressed by Spo0A, as a phosphorylated Spo0A (Spo0A~P) can bind to the only promoter sequence upstream of this locus 53 . While this locus and s B may contribute to DrsbW phenotypic responses, SinR regulates the transcription of other pleiotropic regulators such as s D , Spo0A and CodY, which can regulate many other genes in C. difficile 39,[54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…In B. subtilis , Spo0A is negatively controlled by Spo0E through dephosphorylation, furthermore Spo0E is positively controlled by a σ B promoter 49 . Additionally, it has been suggested that SinR is able to regulate spo0A expression through an unknown mechanism 53 . The SinR homolog in B. subtilis functions as a repressor for the spo0A promoter 57 .…”
Section: Discussionmentioning
confidence: 99%
“…While Spo0A also regulates biofilm formation, flagella production, expression of cell-wall proteins [178] and indirect regulation with the sin locus [176,181,182], modulators like RstA control sporulation and toxin production through the phosphorylation of Spo0A [183]. Three of five orphan kinases (PtpA, PtpB and PtpC) have been reported to negatively regulate sporulation [184,185].…”
Section: Sporulationmentioning
confidence: 99%